Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4314/njbas.v25i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Burning Rates and Water Boiling Time of Wood Charcoal and Briquettes Produced from Carbonized <i>Martynia annua</i> woody Shells

Abstract: This study was conducted to compare the combustion properties of briquettes produced from carbonized Martynia annua woody shells and wood charcoal. Two different briquette samples were produced: Sample (A), is made up of carbonized shells powder plus starch as binding agent while Sample (B), consists of carbonized shells plus waste paper as binding agent. The parameters investigated include calorific value, ignition time, burning rate, and specific fuel consumption. Water boiling time and time taking by the Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
(3 reference statements)
2
2
1
Order By: Relevance
“…From the plot, it could be observed that as the binder proportion increases, the burning rate also increases, which indicates that clay and waste paper binder has significant effects on burning rate. This is contrary to the findings of Hassan et al, (2017) where they reported that a carbonized material blended with waste paper increases the burning rate and thermal conductivity of the briquettes.…”
Section: Discussioncontrasting
confidence: 99%
“…From the plot, it could be observed that as the binder proportion increases, the burning rate also increases, which indicates that clay and waste paper binder has significant effects on burning rate. This is contrary to the findings of Hassan et al, (2017) where they reported that a carbonized material blended with waste paper increases the burning rate and thermal conductivity of the briquettes.…”
Section: Discussioncontrasting
confidence: 99%
“…The burning rate (vcomb) of the samples ranged from 188 to 288 g/h ( Figure 4b); that of charcoal is 333 g/h (Figure 4b). Our findings were almost the same as those found by Hassan et al (2017) for briquettes produced from carbonized Martynia annua woody shells and wood charcoal: 3.68 g/min to 4.76 g/min (equivalent with 220 g/h to 285 g/h). The PG1 and PG2 briquettes sprayed higher amounts of water (Figure 4a).…”
Section: Rate Of Combustion (Vcomb) and Variation Of The Amount Of Wasupporting
confidence: 91%
“…The energy content of our briquettes can be evaluated by exploiting the temperature variation curves of the heated water. The briquette samples BB1, PG2 and PG1 had approximately the same rate of combustion (0.5kg) and ensured the boiling of water (100°C) during 40-80 minutes ( Figure 5); this time was slightly higher than that found by Hassan et al (2017) from 12 to 15 minutes, during the combustion of 225 g to 275 g of briquettes. Their curves representing the temperature variation evolved linearly.…”
Section: Combustion Monitoring Curvesmentioning
confidence: 88%
“…Low volatile matter makes the briquettes to burn slowly and the opposite is true (Ige et al, 2020). This is similar to the findings by Hassan et al (2017), the improvement of fuel ignition time and the burning rate with the increase in binder ratio is due to a higher volatile content (Hassan et al, 2017).…”
Section: Effect Of Binder Ratio On Burning Ratesupporting
confidence: 81%